STRATEGI KEPALA SEKOLAH DALAM MENANGGULANGI KENAKALAN SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI SATU ATAP DESA TELUK, KECAMATAN PEMAYUNG, KABUPATEN BATANG HARI - Hafifah Alawiyah; Fridiyanto; Musa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the forms of student misbehavior, inhibiting factors, and strategies used by the principal to address student misbehavior at SMP Negeri Satu Atap Desa Teluk, Pemayung District, Batang Hari Regency. The study uses a qualitative approach with a descriptive type. Data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman's interactive model, which includes data reduction, data presentation, and conclusion drawing. The results showed that student misbehavior at this school included truancy, foul language, fighting, smoking, and bringing gadgets for purposes unrelated to learning. The main obstacles faced by the principal in addressing student misbehavior were a lack of parental involvement, limited guidance counselors, and weak coordination with external parties. The principal's strategies include preventive approaches (character building and discipline), curative approaches (guidance and educational sanctions), collaborative approaches (cooperation with teachers, parents, and the community), and guidance based on Islamic values and local wisdom. This study concludes that the success of principals' strategies greatly depends on managerial skills, exemplary behavior, and synergy among all components of education.